Effects of yoga (pranayama) on lung function and lactate kinetics in sedentary adults at intermediate altitude (2017)
Introduction: Clinical evidence-based medicine has found increasing benefits of yoga.Objective: To describe the effects on lung function assessed by rest spirometry —vital forced capacity (VFC), forced expiratory volume in one second (FEV1), and FEV1/VFC ratio— in a group of apparently healthy adults, as well as to explore the effects of pranayama techniques in lactate kinetics.Materials and methods: Quasi-experimental study performed in sedentary adults with no prior experience in yoga practice, who received a stimulus during 12 weeks with a minimum frequency of two sessions per week. They were divided into a yoga group (YG) and a control group (CG). Body composition, blood pressure, heart rate, double product (DP), peripheral oxygen saturation (SpO2), blood lactate (Lacts), hematocrit (Htc) by micromethod, and spirometry were determined before and after a training plan with Pranayama. The variables analyzed were forced vital capacity (FVC), forced expiratory volume in one second (FEV1) and FEV1/FVC ratio.Results: Significant differences were found in FVC, FEV1 and lactate among YG and CG (p0.05), and before and after the stimulus in the YG (p0.05). The double product improved in both groups.Conclusions: Targeted practice of pranayama for 12 weeks improved FVC, FEV1, double product (p 0.05) and lactate production capacity (anaerobic capacity).